A Secured e-Tendering Model Based on Rational Unified Process (RUP) Approach: Inception and Elaboration Phases - Haslina Mohd; Fauziah Baharom; Norida Muhd Darus; Mohamed Ali Saip; Zaharin Marzuki; Azman Yasin; Muhammad Afdhal Muhammad Robie (International Journal of Supply Chain Management, 2016)
Due to the rapid rise in the e-Tendering transaction over the internet and the increasing use of e-Tendering solution by large organizations, there is a need to construct a secured e-Tendering model to ensure some security mechanisms such as confidentiality, integrity, and accessibility of the document are embedded in the e-tendering model. This to ensure the e-tendering transaction is secured and the most important is to gain trust from the e-Tendering stakeholder. Therefore, there is a need to develop a secured e-Tendering model as a guideline to e-tendering developers in developing the system. The Rational Unified Process (RUP) is the most appropriate system development methodology that can guide researchers in generating secured artifact. The RUP has been used by many researchers to construct a secured application model in various researches and projects. This due to the ability of the RUP in guiding researchers to deliver secured artifacts through Inception and elaboration phases. Therefore, this study aims to construct a secured e-tendering artifacts based on RUP. The Unified Modeling Language (UML) is used to generate the secured e-tendering artifacts. This paper discusses the generation of use case, misuse case and class diagrams based on security mechanism that need to be embedded in the e-Tendering model. This study also found that, the RUP is one of the best system development methodology that can be used as one of the research methodology in the Software Engineering domain, especially related to secured design of any observed application. This methodology has been tested in various studies, such as in Simulation-based Decision Support, Security Requirement Engineering, Business Modeling and Secure System Requirement, and so forth. . This study may contribute to the software industries in developing a secured system application in the future, and also to the secured system modeling domain.